ENVIRONMENTAL SENSITIVITY OF DESERT SOILTO EROSION IN SOUTHERN AL-QADISIYAH LAKE USING GIS. - Al-Juraisy , Salah M. (Diyala Agricultural Sciences Journal, 2016)
Characterization of soil Sensitivity to erosion in desert ecosystem is very important to conserving fragile ecosystems and planning management and protect ecosystem from degradation . desert ecosystem degradation terms refer to soil erosion, mass movement and basin sedimentation. The study area located in the southern part of Al- Qadisiyah lake (109.15 ha) at latitude from 34°00N to 34°30 N and longitude from 42°00E to 42°20 E. A number of 10 soil site were studied. The soil laboratory analyses were: soil texture, Calcium carbonate content, and average of organic matter content was 0.5%) .The results showed That area of study were classified into four main site varied to soil Sensitivity to erosion which are classified to: law sensitive (12.13%), moderate sensitive (26.90%), high sensitive (39.76%),and very high sensitive (21.21%)